Decision support for parenteral nutrition supplementation in ICU using model-based glycemic control protocol - Abu-Samah A.; Razak N.N.; Suhaimi F.M.; Jamaluddin U.K.; Ralib A.M.; Mat-Nor M.B.; Chase G. (Springer Verlag, 2023)
Biomedical engineering; Decision support systems; Insulin; Intensive care units; Patient treatment; Stochastic models; Stochastic systems; Critically-ill patients; Decision supports; Energy requirements; Enteral nutrition; Glycemic control; Health care providers; Intensive care environments; Parenteral nutritions; Nutrition